The Integration Of Maintenance Requirement Into Development Plan Of Work For Government Building - Khalid, Ellemy Iskandar (2017)
The aims of this research are to integrate and develop a maintenance plan of work for public building through lessons learned from an extensive survey of research literatures on some of the best ideas, approaches, theories, advanced practices practices by the developed countries. In addition, an extensive questionnaire survey of key players and focus group discussions are also held involving the key players in Malaysia. The survey questionnaires involved 312 key players (38% out of 820 predetermined participants).